(untitled) (Bulletin of the International Association for Paleodontology, 2025)
Background: Palatal rugae and tongue morphology have been widely studied for their potential applications in forensic identification and anthropology. Their uniqueness and stability make them valuable markers for gender differentiation. This study aimed to analyse the palatal rugae and tongue morphology in a selected population and assess their applicability in gender identification. Methods: A total of 200 participants (100 males and 100 females) were enrolled in this observational study. Palatal rugae were recorded using maxillary casts and classified based on number, shape, length, direction, and unification. Tongue morphology was assessed using standardized photographs, focusing on shape, border, and fissures. Statistical analysis was conducted to determine gender-based differences. Results: The mean number of total palatal rugae was significantly higher in males (9.13 ± 2.08) compared to females (8.47 ± 1.86, p<0.05). Males exhibited a greater number of straight rugae, while wavy and curved patterns were prevalent in both genders. The most common tongue shape was U-shaped (55%), followed by V-shaped (36.5%) and bifid (8.5%), with significant gender differences (p<0.05). Smooth tongue borders were more frequent in females, whereas scalloped borders were more prevalent in males. Conclusion: The study highlights significant gender differences in palatal rugae patterns and tongue morphology, supporting their utility in forensic identification. These findings reinforce the importance of oral anatomical structures as adjunctive tools in forensic and anthropological studies. Further research incorporating digital analysis techniques may enhance identification accuracy.